Open pit coal mine wheel bucket material taking method - FU HEYING; XU YONGCHAO; MIAO ZHANWEI; TIAN YE; YU XIKAI; WANG HAO; GAO MINGQIANG; ZHAO XU; XIE YUQI; TENG RUIXUE; WANG XIAOGUANG; SUN BAOJIN; et al. (2022)
The open pit coal mine wheel bucket material taking method comprises the following steps that an unloading platform is built, and the unloading platform is provided with an unloading slope surface; the soft rock materials are unloaded to the unloading slope surface; a material taking position is determined, the wheel bucket excavator is moved to the material taking position, and the unloading slope extends around the material taking position; and material taking parameters of the wheel bucket excavator are set, and then a material taking arm of the wheel bucket excavator is driven to swing in the extending direction of the unloading slope so as to take out the soft rock materials. The open pit coal mine wheel bucket material taking method has the advantages of being small in environmental influence and high in material taking efficiency. 本发明公开了一种露天煤矿轮斗取料方法，包括以下步骤：搭建卸载平台，所述卸载平台具有卸载坡面；将软岩物料卸载至所述卸载坡面；确定取料位，并将轮斗挖掘机移动至所述取料位，所述卸载坡面绕着所述取料位延伸；设置所述轮斗挖掘机的取料参数，然后驱动所述轮斗挖掘机的取料臂沿着所述卸载坡面的延伸方向摆动以取出所述软岩物料。本发明实施例的露天煤矿轮斗取料方法具有受